2020
DOI: 10.1155/2020/6134362
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Predisposing Factors, Biomarkers, and Prevention Mechanism of Obesity: A Systematic Review

Abstract: Background. Globally, obesity is becoming a public health problem in the general population. Various determinants were reported by different scholars even though there are inconsistencies. Different biomarkers of obesity were identified for the prediction of obesity. Even though researchers speculate the factors, biomarkers, consequences, and prevention mechanisms, there is a lack of aggregate and purified data in the area of obesity. Summary. In this review, the epidemiology, predisposing factors, biomarkers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 78 publications
0
83
0
11
Order By: Relevance
“…Though conventionally obesity is considered a disease that affects educated and affluent populations, we found that a large proportion of our subjects had not pursued higher education. 22 Furthermore, individuals with obesity are often stigmatised among their peers, which may lead to delays in marriage. In our study population, about one-fifth of women were not married, despite a mean age of 37 years, which traditionally is a very late age for marriage in the Indian context.…”
Section: Resultsmentioning
confidence: 99%
“…Though conventionally obesity is considered a disease that affects educated and affluent populations, we found that a large proportion of our subjects had not pursued higher education. 22 Furthermore, individuals with obesity are often stigmatised among their peers, which may lead to delays in marriage. In our study population, about one-fifth of women were not married, despite a mean age of 37 years, which traditionally is a very late age for marriage in the Indian context.…”
Section: Resultsmentioning
confidence: 99%
“…While chronic underhydration has been associated with obesity [22], other reports suggest hypohydration reduces subsequent food intake [37]. Given the continuing rise in the prevalence of obese individuals and the associated health outcomes [44], research addressing potential contributors to weight gain may help alleviate this major public health problem.…”
Section: Appetitementioning
confidence: 99%
“…Unfortunately, definite strategies to tackle the prevention of obesity, and its related complications, remain elusive. In this regard, epidemiological studies have highlighted some potential environmental exposures, including diet, energy expenditure, early life influences, sleep deprivation, endocrine disruptors, chronic inflammation, and altered gut microbiota (GM) status, as important contributors to a higher obesity risk [13][14][15]. Among these, the GM has received extensive attention during the previous decade because it has been shown that manipulation of the GM may affect the host metabolism.…”
Section: Introductionmentioning
confidence: 99%